Hadith #2116 - Sunan Abi Dawud - Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Ja'far Ghandar ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± ØºÙØ¯Ø± ØµØ§ØØ¨ Ø§ÙÙØ±Ø§Ø¨ÙØ³; Muhammad bin Salmah ÙØÙØ¯ Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¨Ø§ÙÙÙ; Muhammad bin Yahya bin Hiban ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù ØØ¨Ø§Ù; Umar ibn al-Khattab; Uqba bin 'Amir al-Juhayni; Yazid bin Abi Habib ÙØ²ÙØ¯ Ø¨Ù Ø£Ø¨Ù ØØ¨ÙØ¨; Zayd bin Abi Anisa Ø²ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø£ÙÙØ³Ø© (Sunan Abi Dawud)
Abdullah ibn Utbah ibn Masâud said: Abdullah ibn Masâud was informed of this story of a man. The people continued to visit him for a month or visited him many times (the narrator was not sure). He said: In this matter I hold the opinion that she should receive the type of dower given to women of her class with no diminution or excess, observe the waiting period (âiddah) and have her share of inheritance. If it is erroneous, that is from me and from Satan. Allah and His Apostle are free fro
Grade: Sahih

Hadith #2131 - Sunan Abi Dawud - Ali bin al-Mubark al-Hna'iy Ø¹ÙÙ Ø¨Ù Ø§ÙÙØ¨Ø§Ø±Ù Ø§ÙÙÙØ§Ø¦Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Sa'id ibn al-Musayyib Ø³Ø¹ÙØ¯ Ø¨Ù Ø§ÙÙØ³ÙØ¨ Ø¨Ù ØØ²Ù Ø£Ø¨Ù ÙØÙØ¯ Ø§ÙÙØ±Ø´Ù; Uthman bin 'Umar bin Fars Ø¹Ø«ÙØ§Ù Ø¨Ù Ø¹ÙØ± Ø¨Ù ÙØ§Ø±Ø³; Yahya bin Abi Kathir ÙØÙÙ Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ± Ø§ÙØ·Ø§Ø¦Ù (Sunan Abi Dawud)
I married a virgin woman in her veil. When I entered upon her, I found her pregnant. (I mentioned this to the Prophet). The Prophet (ï·º) said: She will get the dower, for you made her vagina lawful for you. The child will be your slave. When she has begotten (a child), flog her (according to the version of al-Hasan). The version of Ibn AbusSari has: You people, flog her, or said: inflict hard punishment on him. Abu Dawud said: This tradition has been transmitted by Qatadah from Saâd b. Yazid
Grade: Da'if

Hadith #2187 - Sunan Abi Dawud - Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Uthman bin 'Umar bin Fars Ø¹Ø«ÙØ§Ù Ø¨Ù Ø¹ÙØ± Ø¨Ù ÙØ§Ø±Ø³ (Sunan Abi Dawud)
Abu Hasan, a client of Banu Nawfal asked Ibn Abbas: A slave had a wife who was a slave-girl. He divorced her by two pronouncements. Afterwards both of them were freed. Is it permissible for him to ask her in marriage again? He said: Yes. This is a decision given by the Messenger of Allah (ï·º).
Grade: Da'if

Hadith #2211 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf Ø¹Ø¨Ø¯ Ø§ÙÙÙØ§Ø¨ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙØ¬ÙØ¯ Ø§ÙØ«ÙÙÙ; Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Ja'far Ghandar ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± ØºÙØ¯Ø± ØµØ§ØØ¨ Ø§ÙÙØ±Ø§Ø¨ÙØ³ (Sunan Abi Dawud)
Abu Tamimah reported from a man of his tribe âThe Prophet (ï·º) heard a man say his wife âO my younger sister! So he prohibited him (addressing his wife in this manner) Abu Dawud said âThis tradition has also been transmitted by âAbd Al Aziz bin Al Mukhtar from Khalid from Abu âUthman from Abu Thamimah from the Prophet (ï·º). This has also been narrated by Shuâbah from Khalid from a man on the authority of Abu Thamimah from the Prophet (ï·º).
Grade: Da'if

Hadith #2307 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø§ÙØ¨ØµØ±Ù Ø§ÙØ³Ø§ÙÙ; Amr bin al-'Aas; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Ja'far bin Abi Kathir ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ±; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Rja'a bin Hywh Ø±Ø¬Ø§Ø¡ Ø¨Ù ØÙÙØ©; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
I can invoke the curse of Allah on anyone who wishes: The smaller surat an-Nisa (i.e. Surat at-Talaq) was revealed after the verse regarding the waiting period of four months and ten days had been revealed.
Grade: Sahih

Hadith #2317 - Sunan Abi Dawud - Azrh bin 'Abdur Rahman Ø¹Ø²Ø±Ø© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø²Ø±Ø§Ø±Ø© Ø§ÙØ®Ø²Ø§Ø¹Ù; Muhammad bin Abi 'Adi ÙØÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø¹Ø¯Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Sa'id bin Abi Sa'id; Sa'id bin Jubayr Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬Ø¨ÙØ± Ø§ÙØ£Ø³Ø¯Ù (Sunan Abi Dawud)
Ibn âAbbas said âThe verse concerning the payment of ransom stands valid for pregnant and sucking woman.â
Grade: Sahih

Hadith #2550 - Sunan Abi Dawud - Anas ibn Malik; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Ja'far bin Abi Kathir ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ±; Shu'bah bin al-Hajjaj Ø´Ø¹Ø¨Ø© Ø¨Ù Ø§ÙØØ¬Ø§Ø¬ (Sunan Abi Dawud)
Abu Hurairah reported the Apostle of Allaah(ï·º) as saying â While a man was going on his way, he felt himself thirsty severely. He found a well and e went down in it. He drank water and came out. Suddenly he saw a dog panting and eating soil due to thirst. The man said (to himself) âThis dog must have reached the same condition due to thirst as I had reached. So he went down into the well, filled his sock with water, held it with his mouth and came up. He supplied water to the dog. Allaah a
Grade: Sahih

Hadith #2581 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø§ÙØ¨ØµØ±Ù Ø§ÙØ³Ø§ÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ï·º) said: There must be no shouting or leading another horse at oneâs side. Yahya added in his tradition: When racing for a wager.
Grade: Sahih

Hadith #2583 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; Mua'dh bin Hisham bin Aby ÙØ¹Ø§Ø° Ø¨Ù ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Sa'id bin Abi al-Hasan Ø³Ø¹ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø§ÙØØ³Ù (Sunan Abi Dawud)
The pommel of the sword of the Messenger of Allah (ï·º) was of silver.
Grade: Sahih

Hadith #2666 - Sunan Abi Dawud - al-Hasan al-Basri Ø§ÙØØ³Ù Ø§ÙØ¨ØµØ±Ù; Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; Mua'dh bin Hisham bin Aby ÙØ¹Ø§Ø° Ø¨Ù ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø© (Sunan Abi Dawud)
The Prophet (ï·º) said: The most merciful of the people in respect of killing are believers (in Allah).
Grade: Da'if

Hadith #2694 - Sunan Abi Dawud - Abu Talha Ansari; Anas ibn Malik; Harun bin 'Abdullah al-Hamal ÙØ§Ø±ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ±ÙØ§Ù Ø§ÙØÙØ§Ù; Mua'dh bin Mua'dh bin Nsr ÙØ¹Ø§Ø° Ø¨Ù ÙØ¹Ø§Ø° Ø¨Ù ÙØµØ±; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Ruh bin 'Ubada bin al-'Ala' Ø±ÙØ Ø¨Ù Ø¹Ø¨Ø§Ø¯Ø© Ø¨Ù Ø§ÙØ¹ÙØ§Ø¡; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ï·º) then said: Return to them (Hawazin) their women and their sons. If any of you withholds anything from this booty, we have six camels for him from the first booty which Allah gives us. The Prophet (ï·º) then approached a camel, and taking a hair from its hump said: O people, I get nothing of this booty, not even this (meanwhile raising his two fingers) but the fifth, and the fifth is returned to you, so hand over threads and needles. A man got up with a ball of hair i
Grade: Hasan

Hadith #2837 - Sunan Abi Dawud - al-Hasan al-Basri Ø§ÙØØ³Ù Ø§ÙØ¨ØµØ±Ù; Muhammad bin Abi 'Adi ÙØÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø¹Ø¯Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Sa'id bin Abi Sa'id; Samra bin Jundub (Sunan Abi Dawud)
The Prophet (ï·º) said: A boy is in pledge for his Aqiqah. Sacrifice is made for him on the seventh day, his head is shaved and is smeared with blood. When Qatadah was asked about smearing with blood, how that should be done, he said: When you cut the head (i.e. throat) of the animal (meant for Aqiqah), you may take a few hair of it, place them on its veins, and then place them in the middle of the head of the infant, so that the blood flows on the hair (of the infant) like a threat. Then its he
Grade: Sahih

Hadith #2858 - Sunan Abi Dawud - ibn Abbas; Masdad bin Masrhad ÙØ³Ø¯Ø¯ Ø¨Ù ÙØ³Ø±ÙØ¯ Ø¨Ù ÙØ³Ø±Ø¨Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Wahb bin Munabbih al-Abnavi ÙÙØ¨ Ø¨Ù ÙÙØ¨Ù Ø§ÙØ£Ø¨ÙØ§ÙÙ; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan Abi Dawud)
The Prophet (ï·º) said: Whatever is cut off of an animal when it is alive is dead.
Grade: Sahih

Hadith #3072 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf Ø¹Ø¨Ø¯ Ø§ÙÙÙØ§Ø¨ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙØ¬ÙØ¯ Ø§ÙØ«ÙÙÙ; Ayoub al-Sakhtiyani Ø£ÙÙØ¨ Ø§ÙØ³Ø®ØªÙØ§ÙÙ; Hisham bin 'Urwa ÙØ´Ø§Ù Ø¨Ù Ø¹Ø±ÙØ©; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Sa'id bin Zayd; Urwa ibn al-Zubayr Ø¹Ø±ÙØ© Ø¨Ù Ø§ÙØ²Ø¨ÙØ± (Sunan Abi Dawud)
The Prophet (ï·º) gave az-Zubayr the land as a fief up to the reach of his horse when he runs. He, therefore, made his horse run until it stopped. He then threw his flog. Thereupon he said: Give him (the land) up to the point where his flog has reached.
Grade: Hasan

Hadith #3123 - Sunan Abi Dawud - Anas ibn Malik; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Shu'bah bin al-Hajjaj Ø´Ø¹Ø¨Ø© Ø¨Ù Ø§ÙØØ¬Ø§Ø¬; Thabit bin Aslam Albanani Ø«Ø§Ø¨Øª Ø¨Ù Ø£Ø³ÙÙ Ø§ÙØ¨ÙØ§ÙÙ; Uthman bin 'Umar bin Fars Ø¹Ø«ÙØ§Ù Ø¨Ù Ø¹ÙØ± Ø¨Ù ÙØ§Ø±Ø³ (Sunan Abi Dawud)
We buried a deceased person in the company of the Messenger of Allah (ï·º). When we had finished, the Messenger of Allah (ï·º) returned and we also returned with him. When he approached his door, he stopped, and we saw a woman coming towards him. He (the narrator) said: I think he recognized her. When she went away, we came to know that she was Fatimah. The Messenger of Allah (ï·º) said to her: What brought you out of your house, Fatimah? She replied: I came to the people of this house, Messenge
Grade: Hasan

Hadith #3143 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø§ÙØ¨ØµØ±Ù Ø§ÙØ³Ø§ÙÙ; Hafsa bint Sirin ØÙØµØ© Ø¨ÙØª Ø³ÙØ±ÙÙ; Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Umm Atiyyah Ansariyah (Sunan Abi Dawud)
We braided her hair in three plaits.
Grade: Sahih

Hadith #3170 - Sunan Abi Dawud - Abdul Samad bin 'Abdul Warith bin Sa'id Ø¹Ø¨Ø¯ Ø§ÙØµÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙØ§Ø±Ø« Ø¨Ù Ø³Ø¹ÙØ¯; Abu Da'ud Ø£Ø¨Ù Ø¯Ø§ÙØ¯ Ø§ÙØ³Ø¬Ø³ØªØ§ÙÙ Ø§ÙØ£Ø²Ø¯Ù; Abu Hurairah; Harb bin Shadaad al-Yashkari ØØ±Ø¨ Ø¨Ù Ø´Ø¯Ø§Ø¯ Ø§ÙÙØ´ÙØ±Ù; Harun bin 'Abdullah al-Hamal ÙØ§Ø±ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙØ±ÙØ§Ù Ø§ÙØÙØ§Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Yahya bin Abi Kathir ÙØÙÙ Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ± Ø§ÙØ·Ø§Ø¦Ù (Sunan Abi Dawud)
I heard the Prophet (ï·º) say: If any Muslim dies and forty men associate nothing with Allah stand over his bier. Allah will accept them as intercessors for him.
Grade: Sahih

Hadith #3196 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø£Ø¨Ù ÙÙÙÙ; Amr bin Murrah bin 'Abdullah Ø¹ÙØ±Ù Ø¨Ù ÙØ±Ø© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø·Ø§Ø±Ù; Hisham bin 'Abdul Malik al-Tayalasi ÙØ´Ø§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø£Ø¨Ù Ø§ÙÙÙÙØ¯ Ø§ÙØ·ÙØ§ÙØ³Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Ja'far bin Abi Kathir ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ±; Shu'bah bin al-Hajjaj Ø´Ø¹Ø¨Ø© Ø¨Ù Ø§ÙØØ¬Ø§Ø¬; Zayd bin Arqam (Sunan Abi Dawud)
The Messenger of Allah (ï·º) passed a grave dug freshly. They arranged a row and uttered four takbirs over it. I asked al-Shaâbi: Who told you ? He replied: A reliable person whom âAbd Allah b. âAbbas attended.
Grade: Sahih

Hadith #3270 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø§ÙØ¨ØµØ±Ù Ø§ÙØ³Ø§ÙÙ; Abdur Rahman bin Abi Bakr; Abu 'Uthman al-Nahdi Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù ÙÙ - Ø£Ø¨Ù Ø¹Ø«ÙØ§Ù Ø§ÙÙÙØ¯Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Sa'id bin Iyas al-Jariri Ø³Ø¹ÙØ¯ Ø¨Ù Ø¥ÙØ§Ø³ Ø§ÙØ¬Ø±ÙØ±Ù; Salm bin Nwh bin Aby Ø³Ø§ÙÙ Ø¨Ù ÙÙØ Ø¨Ù Ø£Ø¨Ù (Sunan Abi Dawud)
Some guests visited us, and Abu Bakr was conversing with the Messenger of Allah (ï·º) at night. He (Abu Bakr) said: I will not return to you until you are free from their entertainment and serving them food. So he brought them food, but they said: We shall not eat it until Abu Bakr comes (back). Abu Bakr then came and asked: What did your guest do? Are you free from their entertainment ? They said: No. I said: I brought them food, but they refused and said: We swear by Allah, we shall not take i
Grade: Sahih

Hadith #3295 - Sunan Abi Dawud - Hisham bin 'Abdul Malik al-Tayalasi ÙØ´Ø§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø£Ø¨Ù Ø§ÙÙÙÙØ¯ Ø§ÙØ·ÙØ§ÙØ³Ù; Hmam bin Yahya bin Dinar ÙÙØ§Ù Ø¨Ù ÙØÙÙ Ø¨Ù Ø¯ÙÙØ§Ø±; Ikrama Ø¹ÙØ±ÙØ©; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø© (Sunan Abi Dawud)
A man came to Prophet (ï·º) and said: Messenger of Allah, my sister has taken a vow to perform hajj on foot. The Prophet (ï·º) said: Allah gets no good from the affliction your sister imposed on herself, so let her perform hajj riding and make atonement for her oath.
Grade: Sahih

Hadith #3297 - Sunan Abi Dawud - Ikrama Ø¹ÙØ±ÙØ©; Khalid bin Mahran al-Hadha' Ø®Ø§ÙØ¯ Ø¨Ù ÙÙØ±Ø§Ù Ø§ÙØØ°Ø§Ø¡; Muhammad bin Abi 'Adi ÙØÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø¹Ø¯Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
That when the Prophet (ï·º) was informed that the sister of âUqbah b. âAmir had taken a vow to perform Hajj on foot, he said: Allah is not in need of her vow. So ask her to ride. Abu Dawud said: Saâib b. âArubah has transmitted a similar tradition. Khalid has also transmitted a similar tradition on the authority of âIkrimah from the Prophet (ï·º).
Grade: Sahih

Hadith #3447 - Sunan Abi Dawud - Abu Da'ud Ø£Ø¨Ù Ø¯Ø§ÙØ¯ Ø§ÙØ³Ø¬Ø³ØªØ§ÙÙ Ø§ÙØ£Ø²Ø¯Ù; Hmam bin Yahya bin Dinar ÙÙØ§Ù Ø¨Ù ÙØÙÙ Ø¨Ù Ø¯ÙÙØ§Ø±; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Yahya bin Fiyyad ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù ÙÙØ§Ø¶; Qatada ÙØªØ§Ø¯Ø© (Sunan Abi Dawud)
The Messenger of Allah (ï·º) as saying: No one withholds goods till their price rises but a sinner. I said to Saâid (b. al-Musayyab): You withhold goods till their price rises. He said: Maâmar used to withhold goods till their price rose. Abu Dawud said: I asked Ahmad (b. Hanbal): What is hoarding (hukrah) ? He replied: That on which people live. Abu Dawud said: Al-Auzaâi said: A muhtakir (one who hoards) is one who withholds supply of goods in the market.
Grade: Sahih

Hadith #3552 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman Ø£Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙÙ; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; Imam Maalik ÙØ§ÙÙ Ø¨Ù Ø£ÙØ³ Ø¨Ù ÙØ§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø¹Ø§ÙØ±; Jabir ibn 'Abdullah; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Yahya bin Hiban ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù ØØ¨Ø§Ù (Sunan Abi Dawud)
A similar tradition has also been transmitted by al-Laith b. Saâd from al-Zuhri, from Abu Salamah from Jabir.
Grade: Sahih

Hadith #3566 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed ØÙÙØ¯ Ø¨Ù Ø£Ø¨Ù ØÙÙØ¯ Ø§ÙØ·ÙÙÙ; Khalid bin Mahran al-Hadha' Ø®Ø§ÙØ¯ Ø¨Ù ÙÙØ±Ø§Ù Ø§ÙØØ°Ø§Ø¡; Masdad bin Masrhad ÙØ³Ø¯Ø¯ Ø¨Ù ÙØ³Ø±ÙØ¯ Ø¨Ù ÙØ³Ø±Ø¨Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan Abi Dawud)
The Messenger of Allah (ï·º) said to me: When my messengers come to you, give them thirty coats of mail, and thirty camels. I asked: Messenger of Allah, is it a loan with a guarantee of its return, or a loan to be paid back? He replied : It is a loan to be paid back.
Grade: Sahih

Hadith #3576 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' ÙØÙØ¯ Ø¨Ù Ø§ÙØ¹ÙØ§Ø¡ - Ø£Ø¨Ù ÙØ±ÙØ¨; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Khazim al-Darir ÙØÙØ¯ Ø¨Ù Ø®Ø§Ø²Ù Ø£Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙØ¶Ø±ÙØ±; Rja'a al-Ansari Ø±Ø¬Ø§Ø¡ Ø§ÙØ£ÙØµØ§Ø±Ù; Sulaiman al-A'mash Ø§ÙØ£Ø¹ÙØ´ / Ø³ÙÙÙØ§Ù Ø¨Ù ÙÙØ±Ø§Ù (Sunan Abi Dawud)
âIf any do fail to judge (by the light of) what Allah has revealed, they are (no better than) unbelieversâ up to âwrongdoers.â These three verses were revealed about the Jews, particularly about Quraizah and al-Nadir.
Grade: Hasan

Hadith #3578 - Sunan Abi Dawud - Abu Burda bin Niyar; Ahmad bin Hanbal Ø£ØÙØ¯ Ø¨Ù ØÙØ¨Ù; Hameed bin Hilal ØÙÙØ¯ Ø¨Ù ÙÙØ§Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qurrah bin Khalid al-Sadusi ÙØ±Ø© Ø¨Ù Ø®Ø§ÙØ¯ Ø§ÙØ³Ø¯ÙØ³Ù; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù (Sunan Abi Dawud)
The Prophet (ï·º) said: If anyone desires the office of Judge and seeks help for it, he will be left to his own devices; if anyone does not desire it, nor does he seek help for it, Allah will send down an angel who will direct him aright. Wakiâ said: (This tradition has also been transmitted) by Israâil, from âAbd al-Aâla, from Bilal bin Abi Musa, from Anas, from the Prophet (ï·º). Abu âAwanah said: from âAbd al-Aâla, from Bilal bin Mirdas al-Fazari, from Khaithamah al-Basri from A
Grade: Da'if

Hadith #3625 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø§ÙØ¨ØµØ±Ù Ø§ÙØ³Ø§ÙÙ; Ikrama Ø¹ÙØ±ÙØ©; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
A man from Muzainah who followed the knowledge and memorized it to me that saâid b.al-Musayyab transmitted it. He then mentioned the rest of the tradition to the same effect.
Grade: Da'if

Hadith #3662 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Mu'adh ibn Jabal; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø© (Sunan Abi Dawud)
The Prophet (ï·º) said: relate traditions from the children of Israâil; there is no harm.
Grade: Sahih

Hadith #3666 - Sunan Abi Dawud - Anas ibn Malik; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Musa bin Khlf al-My ÙÙØ³Ù Ø¨Ù Ø®ÙÙ Ø§ÙØ¹ÙÙ; Qatada ÙØªØ§Ø¯Ø© (Sunan Abi Dawud)
I was sitting in the company of the poor members of the emigrants. Some of them were sitting together because of lack of clothing while a reader was reciting to us. All of a sudden the Messenger of Allah (ï·º) came along and stood beside us. When the Messenger of Allah (ï·º) stood, the reader stopped and greeted him. He asked: What were you doing? We said: Messenger of Allah! We had a reader who was reciting to us and we were listening to the Book of Allah, the Exalted. The Messenger of Allah (ï
Grade: Da'if

Hadith #3710 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Hasan al-Basri Ø§ÙØØ³Ù Ø§ÙØ¨ØµØ±Ù; Khayra Umm al-Hasan al-'Abbassri Ø®ÙØ±Ø© Ø£Ù Ø§ÙØØ³Ù Ø§ÙØ¨ØµØ±Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Yonus bin 'Ubaid bin Dinar ÙÙÙØ³ Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù Ø¯ÙÙØ§Ø± Ø§ÙØ¹Ø¨Ø¯Ù (Sunan Abi Dawud)
We came to the Prophet (ï·º) and said to him: Messenger of Allah, you know who we are, from where we are and to whom we have come. He said: To Allah and His Apostle. We said: Messenger of Allah, we have grapes; what should we do with them? He said: Make them raisins. We then asked: What should we do with raisins? He replied: Steep them in the morning and drink in the evening, and steep them in the evening and drink in the morning. Steep them in skin vessels and do not steep them in earthen jar,
Grade: Sahih

Hadith #3744 - Sunan Abi Dawud - Affan bin Muslim Ø¹ÙØ§Ù Ø¨Ù ÙØ³ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØµÙØ§Ø±; al-Hasan al-Basri Ø§ÙØØ³Ù Ø§ÙØ¨ØµØ±Ù; Hmam bin Yahya bin Dinar ÙÙØ§Ù Ø¨Ù ÙØÙÙ Ø¨Ù Ø¯ÙÙØ§Ø±; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø© (Sunan Abi Dawud)
The Prophet (ï·º) held a wedding feast for Safiyyah with meal and dates.
Grade: Sahih

Hadith #3785 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙØ±Ù Ø§ÙÙÙØ³Ù Ø£Ø¨Ù Ø¹Ø§ÙØ± Ø§ÙØ¹ÙØ¯Ù; Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; ibn Abbas; Ikrama Ø¹ÙØ±ÙØ©; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø© (Sunan Abi Dawud)
The Messenger of Allah (ï·º) prohibited eating the animal which feeds on filth and drinking its milk.
Grade: Sahih

Hadith #3926 - Sunan Abi Dawud - Abbas bin Farroukh al-Jariri Ø¹Ø¨Ø§Ø³ Ø¨Ù ÙØ±ÙØ® Ø§ÙØ¬Ø±ÙØ±Ù; Abdul Samad bin 'Abdul Warith bin Sa'id Ø¹Ø¨Ø¯ Ø§ÙØµÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙØ§Ø±Ø« Ø¨Ù Ø³Ø¹ÙØ¯; Amr bin Shu'aib bin Muhammad Ø¹ÙØ±Ù Ø¨Ù Ø´Ø¹ÙØ¨ Ø¨Ù ÙØÙØ¯ Ø§ÙØ³ÙÙÙ; Hmam bin Yahya bin Dinar ÙÙØ§Ù Ø¨Ù ÙØÙÙ Ø¨Ù Ø¯ÙÙØ§Ø±; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Shu'aib bin Muhammad bin 'Abdullah Ø´Ø¹ÙØ¨ Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ±Ù (Sunan Abi Dawud)
on his fatherâs authority, told that his grandfather reported the Prophet (ï·º) said: A slave who has entered into an agreement to purchase his freedom is a slave as long as a dirham of the agreed price remains to be paid.
Grade: Hasan

Hadith #3934 - Sunan Abi Dawud - Ahmed bin 'Ali al-Nmyry Ø£ØÙØ¯ Ø¨Ù Ø¹ÙÙ Ø§ÙÙÙÙØ±Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Ja'far bin Abi Kathir ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ±; Ruh bin 'Ubada bin al-'Ala' Ø±ÙØ Ø¨Ù Ø¹Ø¨Ø§Ø¯Ø© Ø¨Ù Ø§ÙØ¹ÙØ§Ø¡; Shu'bah bin al-Hajjaj Ø´Ø¹Ø¨Ø© Ø¨Ù Ø§ÙØØ¬Ø§Ø¬ (Sunan Abi Dawud)
A man emancipated his share in a slave. The Prophet (ï·º) allowed his (full) emancipation, and required him to pay the rest of his price.
Grade: Sahih

Hadith #3935 - Sunan Abi Dawud - Ahmed bin 'Ali al-Nmyry Ø£ØÙØ¯ Ø¨Ù Ø¹ÙÙ Ø§ÙÙÙÙØ±Ù; Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; Mua'dh bin Hisham bin Aby ÙØ¹Ø§Ø° Ø¨Ù ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Ruh bin 'Ubada bin al-'Ala' Ø±ÙØ Ø¨Ù Ø¹Ø¨Ø§Ø¯Ø© Ø¨Ù Ø§ÙØ¹ÙØ§Ø¡ (Sunan Abi Dawud)
The Prophet (ï·º) said: If a man emancipates a slave shared by him with another man, his emancipation rests with him (who emancipated his share). This is the version of Ibn Suwaid.
Grade: Sahih

Hadith #3964 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; Ma'dan bin Abi Talha ÙØ¹Ø¯Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø·ÙØØ© ÙÙÙØ§Ù Ø¨Ù Ø·ÙØØ©; Mua'dh bin Hisham bin Aby ÙØ¹Ø§Ø° Ø¨Ù ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Salm bin Abi al-Ja'd Ø³Ø§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ¬Ø¹Ø¯ (Sunan Abi Dawud)
Al-Arif ibn ad-Daylami said: We went to Wathilah ibn al-Asqa and said to him: Tell us a tradition which has not addition or omission. He became angry and replied: One of you recites when his copy of a Qurâan is hung up in his house, and he makes additions and omissions. We said: All we mean is a tradition you have heard from the Messenger of Allah (ï·º). He said: We went to the Prophet (ï·º) about a friend of ours who deserved. Hell for murder. He said: Emancipate a slave on his behalf; Allah
Grade: Hasan

Hadith #4009 - Sunan Abi Dawud - Abu al-Malih; Jarir bin 'Abdul Hameed al-Razi Ø¬Ø±ÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØÙÙØ¯ Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¶Ø¨Ù; Mansur bin al-Ma'tamar al-Salmi ÙÙØµÙØ± Ø¨Ù Ø§ÙÙØ¹ØªÙØ± Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ³ÙÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Ja'far bin Abi Kathir ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ±; Salm bin Abi al-Ja'd Ø³Ø§ÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙØ¬Ø¹Ø¯; Shu'bah bin al-Hajjaj Ø´Ø¹Ø¨Ø© Ø¨Ù Ø§ÙØØ¬Ø§Ø¬ (Sunan Abi Dawud)
The Messenger of Allah (ï·º) forbade to enter the hot baths. He then permitted men to enter them in lower garments.
Grade: Hasan

Hadith #4191 - Sunan Abi Dawud - Abdullah ibn Ja'far; al-Hasan bin Sa'd bin Ma'bad Ø§ÙØØ³Ù Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù ÙØ¹Ø¨Ø¯; Jarir bin Hazim bin Zayd Ø¬Ø±ÙØ± Ø¨Ù ØØ§Ø²Ù Ø¨Ù Ø²ÙØ¯; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Uqba bin Mukaram bin Aflah al-''Ami Ø¹ÙØ¨Ø© Ø¨Ù ÙÙØ±Ù; Wahb bin Jarir bin Hazim bin Zayd ÙÙØ¨ Ø¨Ù Ø¬Ø±ÙØ± Ø¨Ù ØØ§Ø²Ù Ø¨Ù Ø²ÙØ¯ (Sunan Abi Dawud)
The Prophet (ï·º) came to Mecca and he had four plaits of hair.
Grade: Sahih

Hadith #4223 - Sunan Abi Dawud - Hassan ibn Ali bin Abi Talib; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Nwh bin Rabi'ya al-Ansari ÙÙØ Ø¨Ù Ø±Ø¨ÙØ¹Ø© Ø§ÙØ£ÙØµØ§Ø±Ù ÙÙÙØ§ÙÙ Ø£Ø¨Ù ÙÙÙÙ; Sahl bin Hamad Ø³ÙÙ Ø¨Ù ØÙØ§Ø¯ (Sunan Abi Dawud)
A man came to the Prophet (ï·º) and he was wearing a signet-ring of yellow copper. He said to him: How is it that I notice the odour of idols in you? So he threw it away, and came wearing an iron signet ring. He (the Prophet) said: What is it that I see you wearing the adornment of the inhabitants of Hell? So he threw it away. He asked: Messenger of Allah, what material I must use? He said: Make it of silver, but do not weigh it as much as a mithqal, The narrator Muhammad did not say: â âAbd
Grade: Hasan

Hadith #4261 - Sunan Abi Dawud - Abdul Wahid bin Ziyad Ø¹Ø¨Ø¯ Ø§ÙÙØ§ØØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙØ¹Ø¨Ø¯Ù; Abu Kabsha al-Anmari; Affan bin Muslim Ø¹ÙØ§Ù Ø¨Ù ÙØ³ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØµÙØ§Ø±; Asim al-Ahwal Ø¹Ø§ØµÙ Ø§ÙØ£ØÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Yahya bin Hiban ÙØÙØ¯ Ø¨Ù ÙØÙÙ Ø¨Ù ØØ¨Ø§Ù (Sunan Abi Dawud)
The Messenger of Allah (ï·º) said to me: O AbuDharr. I replied: At thy service and at thy pleasure, Messenger of Allah. He then mentioned the tradition in which he said: What will you do when there the death of the people (in Medina) and a house will reach the value of a slave (that is, a grave will be sold for a slave). I replied: Allah and His Apostle know best. Or he said: What Allah and His Apostle choose for me. He said: You must show endurance. Or he said; you may endure. He then said to m
Grade: Sahih

Hadith #4285 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; Mua'dh bin Hisham bin Aby ÙØ¹Ø§Ø° Ø¨Ù ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Salah bin Abi Maryam ØµØ§ÙØ Ø¨Ù Ø£Ø¨Ù ÙØ±ÙÙ Ø§ÙØ¶Ø¨Ø¹Ù - Ø£Ø¨Ù Ø§ÙØ®ÙÙÙ (Sunan Abi Dawud)
The Prophet (ï·º) said: The Mahdi will be of my stock, and will have a broad forehead a prominent nose. He will fill the earth will equity and justice as it was filled with oppression and tyranny, and he will rule for seven years.
Grade: Hasan

Hadith #4287 - Sunan Abi Dawud - Abdullah ibn al-Harith ibn Nawfal; Amr bin 'Asim al-Kalabi Ø¹ÙØ±Ù Ø¨Ù Ø¹Ø§ØµÙ Ø§ÙÙÙØ§Ø¨Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Salah bin Abi Maryam ØµØ§ÙØ Ø¨Ù Ø£Ø¨Ù ÙØ±ÙÙ Ø§ÙØ¶Ø¨Ø¹Ù - Ø£Ø¨Ù Ø§ÙØ®ÙÙÙ; Umm Salamah (Sunan Abi Dawud)
The other narrators mentioned ânine yearsâ from Hisham except Muâadh.
Grade: Da'if

Hadith #4306 - Sunan Abi Dawud - Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ (Sunan Abi Dawud)
The Messenger of Allah (ï·º) said: Some of my people will alight on low-lying ground, which they will call al-Basrah, beside a river called the Tigris over which there is a bridge. Its people will be numerous and it will be one of the capital cities of immigrants (or one of the capital cities of Muslims, according to the version of Ibn Yahya who reported from Abu Maâmar). At the end of time the descendants of Qanturaâ will come with broad faces and small eyes and alight on the bank of the ri
Grade: Hasan

Hadith #4315 - Sunan Abi Dawud - Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Ja'far bin Abi Kathir ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ± (Sunan Abi Dawud)
I know best what the Dajjal (Antichrist) will have with him. He will have with him a sea of water and a river of fire, and what you see as fire will be water and what you sea as water will be fire. If any of you who lives up to that time and desires water, he should drink from what he sees as fire, for he will find it water. Abu Masâud al-Badri said: I heard the Messenger of Allah (ï·º) say in this way.
Grade: Sahih

Hadith #4421 - Sunan Abi Dawud - Jabir bin Samra; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Ja'far bin Abi Kathir ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ±; Shu'bah bin al-Hajjaj Ø´Ø¹Ø¨Ø© Ø¨Ù Ø§ÙØØ¬Ø§Ø¬; Smak bin Hrb bin Aws Ø³ÙØ§Ù Ø¨Ù ØØ±Ø¨ Ø¨Ù Ø£ÙØ³ (Sunan Abi Dawud)
Maâiz ibn Malik came to the Prophet (ï·º) and said that he had committed fornication and he (the Prophet) turned away from him. He repeated it many times, but he (the Prophet) turned away from him. He asked his people: Is he mad? They replied: There is no defect in him. He asked: Have you done it with her? He replied: Yes. so he ordered that he should be stoned to death. He was taken out and stoned to death, and he (the Prophet) did not pray over him.
Grade: Sahih

Hadith #4474 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil Ø§ÙØ¶ØØ§Ù Ø¨Ù ÙØ®ÙØ¯ Ø£Ø¨Ù Ø¹Ø§ØµÙ Ø§ÙÙØ¨ÙÙ; Hassan ibn Ali bin Abi Talib; ibn Abbas; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Ikrama Ø¹ÙØ±ÙØ©; Muhammad bin 'Ali b. al-Hussain al-Baqir ÙØÙØ¯ Ø¨Ù Ø¹ÙÙ Ø¨Ù Ø§ÙØØ³ÙÙ Ø¨Ù Ø¹ÙÙ ,Ø§ÙØ¨Ø§ÙØ±; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ (Sunan Abi Dawud)
When my vindication came down, the Prophet (ï·º) mounted the pulpit and mentioned that, and recited the Qurâan. Then when he came down from the pulpit he ordered regarding the two men and the woman, and they were given the prescribed punishment.
Grade: Hasan

Hadith #4514 - Sunan Abi Dawud - Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; Mua'dh bin Hisham bin Aby ÙØ¹Ø§Ø° Ø¨Ù ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ (Sunan Abi Dawud)
On the authority of his mother than Umm Mubashshir said (Abu Saâid b. al-Aârabi said: So he said it on the authority of his mother ; what is correct is: on the authority of his father, instead of his mother): I entered upon the Prophet (ï·º). He then mentioned the tradition of Makhlad b. Khalid in a way similar to the tradition of Jabir. The narrator said: Then Bishr b. al-Baraâ b. Maârur died. So he (the Prophet) sent for the Jewess and said: What did motivate you for your work you have
Grade: Sahih

Hadith #4552 - Sunan Abi Dawud - Amr bin al-Aswad al-Ansi Ø¹ÙØ±Ù Ø¨Ù Ø§ÙØ£Ø³ÙØ¯ Ø§ÙØ¹ÙØ³Ù; Muhammad bin 'Abdullah bin Qahzad ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙØ²Ø§Ø¯; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Sa'id bin Abi Sa'id; Uthman ibn 'Affaan (Sunan Abi Dawud)
The bloodwit for unintentional murder is in four parts: twenty five she-camels in their fourth year, twenty five she-camels in their fifth year, twenty five she-camels in their third year, and twenty twenty five she-camels in their second year.
Grade: Da'if

Hadith #4553 - Sunan Abi Dawud - Abu Da'ud Ø£Ø¨Ù Ø¯Ø§ÙØ¯ Ø§ÙØ³Ø¬Ø³ØªØ§ÙÙ Ø§ÙØ£Ø²Ø¯Ù; al-Qasim bin Salam Ø§ÙÙØ§Ø³Ù Ø¨Ù Ø³ÙØ§Ù; Muhammad bin 'Abdullah bin Qahzad ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙØ²Ø§Ø¯; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qatada ÙØªØ§Ø¯Ø©; Sa'id bin Abi Sa'id; Sa'id ibn al-Musayyib Ø³Ø¹ÙØ¯ Ø¨Ù Ø§ÙÙØ³ÙØ¨ Ø¨Ù ØØ²Ù Ø£Ø¨Ù ÙØÙØ¯ Ø§ÙÙØ±Ø´Ù; Zayd ibn Thabit (Sunan Abi Dawud)
The bloodwit for what resembled intentional murder should be forty pregnant she-camels in their fifth year, thirty she-camels in their fourth year, and thirty she-camels in their third year. The bloodwit for unintentional murder is thirty she-camels in their fourth year, thirty she-camels in their third year, and twenty she-camels in their second year.
Grade: Da'if

Hadith #4621 - Sunan Abi Dawud - Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qurrah bin Khalid al-Sadusi ÙØ±Ø© Ø¨Ù Ø®Ø§ÙØ¯ Ø§ÙØ³Ø¯ÙØ³Ù; Yahya bin Kathir bin Darham ÙØÙÙ Ø¨Ù ÙØ«ÙØ± Ø¨Ù Ø¯Ø±ÙÙ Ø§ÙØ¹ÙØ¨Ø±Ù (Sunan Abi Dawud)
I was a prisoner in Syria. A man called me from behind. I turned towards him and suddenly found that it was Raja b. Haiwah. He said: Abu âAwn, what is this that the people are telling about al-Hasan? I said: They are much lying to al-Hasan.
Grade: Sahih

Hadith #4622 - Sunan Abi Dawud - Abdullah bin 'Awn bin Artaban Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙÙ Ø¨Ù Ø£Ø±Ø·Ø¨Ø§Ù Ø§ÙØ®Ø²Ø§Ø±; Hammad bin Zayd ØÙØ§Ø¯ Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø¯Ø±ÙÙ Ø§ÙØ£Ø²Ø¯Ù Ø§ÙØ£Ø²Ø±Ù; Mu'ml bin Isma'il al-Dwy Mwla ÙØ¤ÙÙ Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ Ø§ÙØ¹Ø¯ÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø± (Sunan Abi Dawud)
I heard Ayyub say: Two kinds of people have lied to al-Hasan: people who believed in free will and they intended that they publicise their belief by it; and people who had enmity with and hostility (for al-Hasan), saying: Did he not say so and so? Did he not say so and so?
Grade: Sahih

Hadith #4632 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; al-Hasan al-Basri Ø§ÙØØ³Ù Ø§ÙØ¨ØµØ±Ù; Ash'uth bin Qays; Muhammad bin 'Abdullah al-Ansari ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø§ÙÙØ«ÙÙ - Ø§ÙØ£ÙØµØ§Ø±Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ (Sunan Abi Dawud)
Abu Hurairah said that a man came to the Messenger of Allah (ï·º) and said: I saw (in my dream) a piece of cloud from which ghee and honey were dropping. I saw the people spreading their hands. Some of them took much and some a little. I also saw a rope hanging from Heaven to Earth. I saw, Messenger of Allah, that you caught hold of it and ascended by it. Then another man caught hold of it and ascended it. Then another man caught hold of it and ascended it. Then another man caught hold of it, bu
Grade: Sahih

Hadith #4635 - Sunan Abi Dawud - Affan bin Muslim Ø¹ÙØ§Ù Ø¨Ù ÙØ³ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØµÙØ§Ø±; Hammad bin Salama ØÙØ§Ø¯ Ø¨Ù Ø³ÙÙØ©; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Samra bin Jundub (Sunan Abi Dawud)
One day the Prophet (ï·º) asked: Which of you had a dream? He then mentioned the rest of the tradition to the same effect, but he did not mention the word âdislikedâ. Instead, he said: The Messenger of Allah (ï·º) was grieved about that. He then said: There will be a caliphate on the model of prophecy, then Allah will give the kingdom to whom he wills.
Grade: Sahih

Hadith #4660 - Sunan Abi Dawud - Abu Bakra al-Thaqafi; al-Hasan al-Basri Ø§ÙØØ³Ù Ø§ÙØ¨ØµØ±Ù; Ali bin Zayd bin 'Abdullah bin Zuhayr Ø¹ÙÙ Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø²ÙÙØ±; Ash'uth bin Qays; Hammad bin Zayd ØÙØ§Ø¯ Ø¨Ù Ø²ÙØ¯ Ø¨Ù Ø¯Ø±ÙÙ Ø§ÙØ£Ø²Ø¯Ù Ø§ÙØ£Ø²Ø±Ù; Masdad bin Masrhad ÙØ³Ø¯Ø¯ Ø¨Ù ÙØ³Ø±ÙØ¯ Ø¨Ù ÙØ³Ø±Ø¨Ù; Muhammad bin 'Abdullah al-Ansari ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø§ÙÙØ«ÙÙ - Ø§ÙØ£ÙØµØ§Ø±Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muslim bin Ibrahim al-Azdy ÙØ³ÙÙ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ Ø§ÙØ£Ø²Ø¯Ù Ø§ÙÙØ±Ø§ÙÙØ¯Ù (Sunan Abi Dawud)
When the illness of the Messenger of Allah (ï·º) became serious while I was with him among a group of people, Bilal called him for prayer. He said: Ask someone to lead the people in prayer. So Abdullah ibn Zamâah went out and found that Umar was present among the people and AbuBakr was not there. I said: Umar, get up and lead the people in prayer. So he came forward and uttered âAllah is Most Greatâ. When the Messenger of Allah (ï·º) heard his voice, as Umar had a loud voice, he said: Wher
Grade: Hasan Sahih

Hadith #4724 - Sunan Abi Dawud - Abdul A'ala bin Hamad bin Nasr al-Bahli Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ Ø¨Ù ØÙØ§Ø¯ Ø¨Ù ÙØµØ± Ø§ÙØ¨Ø§ÙÙÙ Ø§ÙÙØ±Ø³Ù; Ahmed bin Sa'id bin Ibrahim Ø£ØÙØ¯ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ Ø§ÙØ±Ø¨Ø§Ø·Ù; Ibn Ishaq ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø¨Ù ÙØ³Ø§Ø±â; Jarir bin Hazim bin Zayd Ø¬Ø±ÙØ± Ø¨Ù ØØ§Ø²Ù Ø¨Ù Ø²ÙØ¯; Jbyr bin Muhammad bin Jbyr Ø¬Ø¨ÙØ± Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¬Ø¨ÙØ±; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Wahb bin Jarir bin Hazim bin Zayd ÙÙØ¨ Ø¨Ù Ø¬Ø±ÙØ± Ø¨Ù ØØ§Ø²Ù Ø¨Ù Ø²ÙØ¯; Y'aqub bin 'Utba bin al-Mughira ÙØ¹ÙÙØ¨ Ø¨Ù Ø¹ØªØ¨Ø© Ø¨Ù Ø§ÙÙØºÙØ±Ø© Ø¨Ù Ø§ÙØ£Ø®ÙØ³ (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Simak through a different chain of narrators to the same effect.
Grade: Da'if

Hadith #4911 - Sunan Abi Dawud - Aisha bint Abi Bakr; Hisham bin 'Urwa ÙØ´Ø§Ù Ø¨Ù Ø¹Ø±ÙØ©; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Khalid bin Athmh ÙØÙØ¯ Ø¨Ù Ø®Ø§ÙØ¯ Ø¨Ù Ø¹Ø«ÙØ©; Urwa ibn al-Zubayr Ø¹Ø±ÙØ© Ø¨Ù Ø§ÙØ²Ø¨ÙØ± (Sunan Abi Dawud)
it is not allowable for a Muslim to keep apart from his brother for more than three days. When they meet, this turns away from him, and that turns away from him. The better of the two is the one who initiates in salutation.
Grade: Sahih

Hadith #4993 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙØ±Ù Ø§ÙÙÙØ³Ù Ø£Ø¨Ù Ø¹Ø§ÙØ± Ø§ÙØ¹ÙØ¯Ù; Ali bin Abd al-A'la Ø¹ÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ£Ø¹ÙÙ; Ibrahim bin Tahman Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù Ø·ÙÙØ§Ù; Muhammad bin al-Fadl 'Aram ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ¶Ù Ø§ÙØ³Ø¯ÙØ³Ù Ø£Ø¨Ù Ø§ÙÙØ¹ÙØ§Ù Ø¹Ø§Ø±Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Zayd bin Arqam (Sunan Abi Dawud)
The Prophet (ï·º) said: To harbour good thoughts is a part of well-conducted worship. (This is according to Nasrâs version). Abu Dawud said: Mahnaâ is reliable and he is from Basrah.
Grade: Hasan

Hadith #5038 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman Ø£Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙÙ; Hisham bin Abi 'Abdullah al-Dastawa'i ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¯Ø³ØªÙØ§Ø¦Ù; Mua'dh bin Hisham bin Aby ÙØ¹Ø§Ø° Ø¨Ù ÙØ´Ø§Ù Ø¨Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Yahya bin Abi Kathir ÙØÙÙ Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ± Ø§ÙØ·Ø§Ø¦Ù (Sunan Abi Dawud)
The Jews used to try to sneezes in the presence of the Prophet (ï·º) hoping that he would say to them: âAllah have mercy on you!â but he would say: May Allah guide you and grant you well-being!
Grade: Sahih

Hadith #5039 - Sunan Abi Dawud - Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Salm bin Nwh bin Aby Ø³Ø§ÙÙ Ø¨Ù ÙÙØ Ø¨Ù Ø£Ø¨Ù; Umar bin Jabir al-Yemami Ø¹ÙØ± Ø¨Ù Ø¬Ø§Ø¨Ø± Ø§ÙÙÙØ§ÙÙ (Sunan Abi Dawud)
Two men sneezed in the presence of the prophet (May peace be upon him). He said : Allah have mercy on you! To one and not to the other. He was asked: Messenger of Allah! Two persons sneezed. Ahmadâs version has: You invoked a blessing on one of them and left the other. He replied : This man praised Allah, and this man did not praise Allah.
Grade: Sahih

Hadith #5088 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari Ø¹Ø¨Ø§Ø³ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø¸ÙÙ Ø§ÙØ¹ÙØ¨Ø±Ù; Abd al-Jlyl bin Atyh Ø¹Ø¨Ø¯ Ø§ÙØ¬ÙÙÙ Ø¨Ù Ø¹Ø·ÙØ© Ø§ÙÙÙØ³Ù Ø£Ø¨Ù ØµØ§ÙØ; Abdur Rahman bin Abi Bakra Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙØ±Ø©; Abu 'Amir al-'Aqdi Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙØ±Ù Ø§ÙÙÙØ³Ù Ø£Ø¨Ù Ø¹Ø§ÙØ± Ø§ÙØ¹ÙØ¯Ù; Ja'far bin Maymun al-Tamimi Ø¬Ø¹ÙØ± Ø¨Ù ÙÙÙÙÙ Ø§ÙØªÙÙÙÙ Ø¨ÙØ§Ø¹ Ø§ÙØ£ÙÙØ§Ø·; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ (Sunan Abi Dawud)
Aban ibn Uthman said: I heard Uthman ibn Affan (his father) say: I heard the Messenger of Allah (ï·º) say: If anyone says three times: âIn the name of Allah, when Whose name is mentioned nothing on Earth or in Heaven can cause harm, and He is the Hearer, the Knowerâ he will not suffer sudden affliction till the morning, and if anyone says this in the morning, he will not suffer sudden affliction till the evening. Aban was afflicted by some paralysis and when a man who heard the tradition beg
Grade: Sahih

Hadith #5105 - Sunan Abi Dawud - Abdul 'Aziz bin Jurayj Ø¹Ø¨Ø¯ Ø§ÙØ¹Ø²ÙØ² Ø¨Ù Ø¬Ø±ÙØ¬; Da'ud bin 'Abdur Rahman al-'Atar Ø¯Ø§ÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø§ÙØ¹Ø·Ø§Ø±; Ibn Jurayj Ø§Ø¨Ù Ø¬Ø±ÙØ¬; Ibrahim bin Abi al-Wzyr Akhw Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù Ø£Ø¨Ù Ø§ÙÙØ²ÙØ±; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ (Sunan Abi Dawud)
I saw the Messenger of Allah (ï·º) uttering the call to prayer (Adhan) in the ear of al-Hasan ibn Ali when Fatimah gave birth to him.
Grade: Hasan

Hadith #5126 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø¹ÙÙØ± Ø¨Ù Ø³ÙÙØ¯ Ø§ÙÙØ¨Ø·Ù; Abu Hurairah; Abu Salama bin 'Abdur Rahman Ø£Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙÙ; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Shayban bin 'Abdur Rahman Ø´ÙØ¨Ø§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø§ÙÙØÙÙ Ø£Ø¨Ù ÙØ¹Ø§ÙÙØ©; Yahya bin Abi Bkyr ÙØÙÙ Ø¨Ù Ø£Ø¨Ù Ø¨ÙÙØ± ÙØ§Ø³ÙÙ ÙØ³Ø± (Sunan Abi Dawud)
Messenger of Allah! A man loves some people, but he cannot do work like their work. He replied; Yes, Abu Dharr, will be with those whom you love. Abu Dharr then repeated it. The Messenger of Allah (May peace be upon him) also repeated it.
Grade: Sahih

Hadith #5142 - Sunan Abi Dawud - Abu al-Tufayl, 'Amir bin Wathla; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil Ø§ÙØ¶ØØ§Ù Ø¨Ù ÙØ®ÙØ¯ Ø£Ø¨Ù Ø¹Ø§ØµÙ Ø§ÙÙØ¨ÙÙ; Amarah bin Thuban Ø¹ÙØ§Ø±Ø© Ø¨Ù Ø«ÙØ¨Ø§Ù ØØ¬Ø§Ø²Ù; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ (Sunan Abi Dawud)
While we were with the Messenger of Allah! (ï·º) a man of Banu Salmah came to Him and said: Messenger of Allah is there any kindness left that I can do to my parents after their death? He replied: Yes, you can invoke blessings on them, forgiveness for them, carry out their final instructions after their death, join ties of relationship which are dependent on them, and honour their friends.
Grade: Hasan

Hadith #5157 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' ÙØÙØ¯ Ø¨Ù Ø§ÙØ¹ÙØ§Ø¡ - Ø£Ø¨Ù ÙØ±ÙØ¨; Abu Mas'ud al-Badri; Ibrahim bin Yazid - Taym al-Rabab Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù ÙØ²ÙØ¯ Ø¨Ù Ø´Ø±ÙÙ ØªÙÙ Ø§ÙØ±Ø¨Ø§Ø¨; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Muhammad bin Khazim al-Darir ÙØÙØ¯ Ø¨Ù Ø®Ø§Ø²Ù Ø£Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙØ¶Ø±ÙØ±; Sulaiman al-A'mash Ø§ÙØ£Ø¹ÙØ´ / Ø³ÙÙÙØ§Ù Ø¨Ù ÙÙØ±Ø§Ù; Yazid bin Sharayk bin Tariq ÙØ²ÙØ¯ Ø¨Ù Ø´Ø±ÙÙ Ø¨Ù Ø·Ø§Ø±Ù Ø§ÙØªÙÙÙ Ø§ÙÙÙÙÙ (Sunan Abi Dawud)
I saw Abu Dharr at Rabadhah. He was wearing a thick cloak, and his slave also wore a similar one. He said : the people said: Abu Dharr! (it would be better) if you could take the cloak which your slave wore, and you combined that with, and it would be a pair of garments (hullah) and you would clothe him with another garment. He said: Abu Dharr said : I abused a man whose mother was a non-Arab and I reviled him for his mother. He complained against me to the apostle of allah (May peace be upon hi
Grade: Sahih

Hadith #5183 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹ÙØ±Ù Ø£Ø¨Ù Ø¹ÙØ±Ù Ø§ÙØ£ÙØ²Ø§Ø¹Ù; al-Waleed bin Muslim bin Shahab Ø§ÙÙÙÙØ¯ Ø¨Ù ÙØ³ÙÙ Ø¨Ù Ø´ÙØ§Ø¨; Muhammad bin 'Abdur Rahman bin Sa'd ÙØÙØ¯ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø²Ø±Ø§Ø±Ø©; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Qays ibn Sa'd ibn 'Ubadah; Yahya bin Abi Kathir ÙØÙÙ Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ± Ø§ÙØ·Ø§Ø¦Ù (Sunan Abi Dawud)
âUmar said to Abu Musa : I do not blame you, but the matter of transmitting a tradition from the Messenger of Allah (May peace be upon him) is serious.
Grade: Sahih

Hadith #5201 - Sunan Abi Dawud - Anas ibn Malik; Hameed bin Abi Hameed ØÙÙØ¯ Ø¨Ù Ø£Ø¨Ù ØÙÙØ¯ Ø§ÙØ·ÙÙÙ; Khalid bin al-Harith bin 'Ubaid Ø®Ø§ÙØ¯ Ø¨Ù Ø§ÙØØ§Ø±Ø« Ø¨Ù Ø¹Ø¨ÙØ¯; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ (Sunan Abi Dawud)
Umar came to the Prophet (ï·º) when he was in his wooden oriel, and said to him: Peace be upon you. Messenger of Allah, peace be upon you! May Umar enter ?
Grade: Sahih